2012
DOI: 10.1007/s12079-012-0183-1
|View full text |Cite
|
Sign up to set email alerts
|

CCN2 exerts direct cytoprotective actions in adult cardiac myocytes by activation of the PI3-kinase/Akt/GSK-3β signaling pathway

Abstract: We recently reported that transgenic mice with cardiac-restricted overexpression of CCN2/CTGF have substantially increased tolerance towards ischemia/reperfusion injury. The purpose of this study was to investigate to what extent fully differentiated cardiac myocytes are direct targets of CCN2, and to resolve the signaling mechanisms that convey the cardioprotective actions of CCN2. Akt and GSK-3β were identified as putative intermediaries of intracellular signaling stimulated by recombinant human CCN2 (rhCCN2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 23 publications
3
24
0
Order By: Relevance
“…For instance, it has reported that combination of chemokine (C-C motif) ligand 2 (CCL2) and sialic acid binding Ig-like lectin 9 (SIGLEC9), which are produced from DPSCs, is needed to enhance repair of the spinal cord [27]. We identified several secreted factors which have been reported as cardioprotective, including CTGF, MYDGF, DKK3, and follistatin like 1 (FSTL1) [21,[28][29][30]. However, single treatment of CTGF, DKK3 and FSTL1, did not enhance cell viability in an in vitro OGD-assay (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has reported that combination of chemokine (C-C motif) ligand 2 (CCL2) and sialic acid binding Ig-like lectin 9 (SIGLEC9), which are produced from DPSCs, is needed to enhance repair of the spinal cord [27]. We identified several secreted factors which have been reported as cardioprotective, including CTGF, MYDGF, DKK3, and follistatin like 1 (FSTL1) [21,[28][29][30]. However, single treatment of CTGF, DKK3 and FSTL1, did not enhance cell viability in an in vitro OGD-assay (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent work, it was convincingly demonstrated that neither its heart-specific deletion nor its overexpression had any influence on cardiac remodeling and function with aging or after multiple stress stimuli [44]. This is in sharp contrast to other mouse studies demonstrating either a beneficial effect of CTGF for cardiomyocyte survival or a detrimental effect on cardiac fibrosis after TAC [8][9][10][11]. Thus further unbiased studies like secretome analyses have to be performed in order to identify responsible factors downstream of p63RhoGEF-RhoA explaining the observed changes in tissue properties.…”
mentioning
confidence: 89%
“…By anchoring to the ECM, CTGF is thought to coordinate the micro-milieu in the myocardium by keeping diverse growth factors in close vicinity to cardiac cells and their receptors. However, in vivo data on the role of CTGF are surprisingly conflicting ranging from a pro-fibrotic to a cardiomyocyte protective function [8][9][10][11]. Similar to the still obscure role of CTGF, there is not much data available how the regulation of CTGF expression and secretion is achieved in cardiac cells.…”
Section: Introductionmentioning
confidence: 99%
“…GSK-3β is tightly regulated by the survival pathway represented by phosphatidylinositol-3 kinase (PI3K) and its downstream effector the protein kinase B (Akt) (Moe et al, 2013). Accumulating evidence has shown that nuclear translocation of Nrf2 might be induced by a decrease of GSK-3β phosphorylation (Ser9) (Rojo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%